2021
DOI: 10.1007/s00259-021-05237-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting biochemical response and survival benefits following radioligand therapy with [177Lu]Lu-PSMA in metastatic castrate-resistant prostate cancer: a review

Abstract: Background Prostate cancer (PC) is one of the most common cancers in men. Although the overall prognosis is favorable, the management of metastatic castration-resistant prostate cancer (mCRPC) patients is challenging. Usually, mCRPC patients with progressive disease are considered for radioligand therapy (RLT) after exhaustion of other standard treatments. The prostate-specific membrane antigen (PSMA) labeled with Lutetium-177 ([177Lu]Lu-PSMA) has been widely used, showing favorable and successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Moreover, in the present study, response was assessed only using the PSA change after two cycles of 177 Lu-PSMA-RLT. Although easily to obtain in clinical routine and demonstrating a high predictive value for later outcome [13], Han et al recently revealed significant discordance between PSA and follow-up PSMA-PET/CTs for response assessment pooling 10 different studies [35]. Nonetheless future studies should also include follow-up PSMA-PET/CTs for response assessment (including early biochemical response and OS) to further define the value of changes in PET parameters, such as delta values of PSMA-TV, TL-PSMA or occurrence of new metastases for subsequent outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the present study, response was assessed only using the PSA change after two cycles of 177 Lu-PSMA-RLT. Although easily to obtain in clinical routine and demonstrating a high predictive value for later outcome [13], Han et al recently revealed significant discordance between PSA and follow-up PSMA-PET/CTs for response assessment pooling 10 different studies [35]. Nonetheless future studies should also include follow-up PSMA-PET/CTs for response assessment (including early biochemical response and OS) to further define the value of changes in PET parameters, such as delta values of PSMA-TV, TL-PSMA or occurrence of new metastases for subsequent outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ongoing prospective VISION phase-3 trial further investigates the clinical value of PSMA RLT and hence may further boost the use of RLT in mCRPC patients [12]. Most studies demonstrated PSA response in about half of the enrolled subjects, whereas 30% of the patients still suffered from progressive disease (PSA increase of >25%) [13]. Therefore, predictors for identifying such high-risk individuals are intensively sought, and multiple studies have already investigated the use of PSMA-ligand PET/CT for late outcome, e.g., in terms of overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a meta-analysis revealed that increased ALP and CRP had worse OS, whereas baseline PSA, PLT, and WBC had no impact on OS. 33 Besides, the impact of baseline LDH, Hg, age, and prior chemotherapy is controversial based on the meta-analysis. Tumor burden is also a critical point for therapy of choice since the CHAARTED study showed that low volume M1 disease did not benefit from DTX as much as high volume disease.…”
Section: Discussionmentioning
confidence: 99%
“…To refine therapeutic reasoning in RLT, early denominators of treatment efficacy are highly desired. Various predictive factors for both response and outcome have been put forth, mainly based on retrospective evidence from heterogeneous patient groups [34].…”
Section: Discussionmentioning
confidence: 99%